Safe to Breathe Analyses and Recommendations for Improving Ambient Air Quality Management in Ethiopia - Xie, Jian (World Bank, Washington, DC, 2021)
This report is the synthesis of the key findings and recommendations of the studies carried out under the World Bank’s Advisory Services & Analytics program entitled “Ethiopia: Air Quality Management and Urban Mobility.” The report is organized as follows. After an introduction, Chapter two is an overview of air pollution issues, including air pollutants and impacts, the air quality situation in Addis Ababa (AA), and institutional arrangements for AQM in Ethiopia. Chapter three assesses the health impact of air pollution in AA and valuates its economic costs. Chapter four summarizes the study results of emission inventory and source apportionment, while Chapter five proposes and prioritizes the mitigation measures for transport air pollution control. The final chapter provides recommendations and a road map that Ethiopia might take to address emerging air pollution problems and improve AQM nationwide and in AA over the next ten years.